Isolation of the biofilm producing bacteria from osteomyelitis patients at Hospital Tengku Ampuan Afzan (HTAA), Kuantan - Yaacob, Khairul Ikhwan; Mohd Yusof, Nazri; Mohamed, Farahidah; Mohd Shafri, Mohd Affendi (Malaysian Society for Microbiology, 2015)
Aims: Accurate diagnosis and proper treatments of osteomyelitis are often difficult and ineffective due to several reasons such as less sensitive sample collected and the formation of biofilm following prosthetic use. Thus, our goal of this study is to identify suitable sample for laboratory diagnosis and also microbial species that cause osteomyelitic infection and discriminate between biofilm and non-biofilm producing strains in patients at Hospital Tengku Ampuan Afzan, Kuantan. Methodology and results: Samples of bone, prosthetic material, tissue and swab were collected from patient with suspected osteomyelitis at the hospital. Bacteria were isolated from sample using methods such as homogenization, direct transfer, and sonication. Then, species identification was done by colony characterization, biochemical test and the API identification system. Once species identified, tissue culture plate method was performed to discriminate the biofilm-producing strain from the non-biofilm-producing strain. The total number of 57 samples were collected from 17 cases of suspected osteomyelitis with 34 samples were found positive bacterial growth. Prosthetic samples produced highest positive growth with 81.3%, following by bone samples with 66.7% while swab and tissue samples with 46.2% and 43.8% respectively. We found that 14 from total 16 pathogens identified were biofilm producing-strains. Conclusion, significance, and impact of study: Prosthetic and bone samples produced higher bacterial growth, in contrast to other type of samples. Sonication method improves bacterial detection. Biofilm producing-bacteria were also the most common isolated strains from osteomyelitic infection. These have underscored the need to revise current clinical and laboratory practice as proper identification biofilm bacteria may influences management an outcome.